COAL WORKER’S PNEUMOCONIOSIS - Rinawati, Putri (Majority, 2015)
Abstract Coal workers’ pneumoconiosis (CWP) is a chronic occupational lung disease caused by long-term inhalation of dust, which triggers inflammation of the alveoli, eventually resulting in irreversible lung damage. CWP ranges in severity from simple to advanced; the most severe form is progressive massive fibrosis (PMF). WHO said that 1,1 thousand mortality caused by working and 5% from this mortality is Pneumoconiosis and 6 % from this pneumoconiosis are CWP (Coal Worker’s Pneumokoniosis). Prevalency Coal Worker’s Pneumoconiosis in Indonesia only do in some place of work. There are three point of CWP for diagnose. First, exposure dust inhale from coal miners; second, abnormality radiograph of lung; and third, amormality respiration. Some examination for diagnose CWP are Phycical Examination, Laboratorium Examination, Sprirometry test, and Radiography test (Thorax radiography and CT Scan). The average interval from a normal chest radiograph to massive fibrosis was 12 years. To prevent pneumoconiosis in surface miners, operations should use effective dust monitoring and control methods to reduce respiratory hazards and emphasize the risk for advanced pneumoconiosis in worker training. CDC’s National Institute for Occupational Safety and Health recommends that surface coal miners be included in periodic health surveillance. Keywords: coal worker”s pneumoconiosis, diagnose, prevalency, preventive Abstrak Pneumoconiosis batu bara adalah penyakit dalam pekerjaan yang kronik akibat menghirup debu dalam waktu yang lama, dengan ditandai adanya inflamasi di alveolus, sehingga berdampak pada kelainan paru yang irreversible. Tingkat keparahan pneumoconiosis batu bara mulai dari ringan sampai berat; yang paling berat adalah Progressive Massive Fibrosis (PMF). WHO menyatakan 1,1 juta kematian adalah akibat pekerjaan dan 5% dari kematian tersebut adalah pneumoconiosis, dan dari 6% dari pneumoconiosis ini adalah Pneumoconiosis batu bara. Prevalensi Pneumoconiosis batu bara di Indonesia hanya dilakukan di berbagai tempat kerja saja. Ada tiga kriteria dalam mendiagnosis Pneumokoniosis batu bara. Pertama, pajanan debu batu bara; kedua, gambaran radiologi paru yang abnormal; ketiga, gangguan fungsi pernapasan. Beberapa pemeriksaan untuk mendiagnosa Pneumoconiosis batu bara adalah pemeriksaan fisik, pemeriksaan laboratorium, tes spirometri, dan pemeriksaan radiografi ( foto thorax dan CT csan). Intrerval dari pemeriksaan radiografi normal menjadi fibrosis masif adalah 12 tahun. Untuk mencegah pneumokoniosis pada penambang, operasi harus dilakukan dengan monitoring debu dan mengontrol beberapa metode untuk menurunkan kerugian pada pernapasan dan mengurangi resiko dengan melakukan training pada pekerja. CDC’s National Institute for Occupational Safety and Health merekomendasi agar pekerja batu bara dimasukan dalam surveilans kesehatan. Kata kunci: diagnosis, pencegahan, pneumoconiosis batu bara, prevalensi